Social Media Strategies by the Sobat Icad Community to Support Richard Eliezer as a Justice Collaborator - Celesta, Xiantira Ghassani; Parani, Rizaldi; Geraldine, Christa Olivia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The Sobat Icad community uses social media to express their aspirations in supporting Richard Eliezer as a justice collaborator in the case of Brigadier J's murder. Through this study, the researchers identified the strategies used by Sobat Icad community in utilizing social media as a platform to provide support through campaigns. The research was conducted based on the Stimulus-Organism- Response theory by Carl Hovland and the Campaign Concept by Anne Gregory. The researchers employed a descriptive qualitative approach with a case study research method. The study results showed the existence of social media usage strategies formulated by Sobat Icad community in conducting their campaigns. This includes the selection of social media platforms that are Instagram and WhatsApp, the choice of content using photos, posters, and videos, as well as the establishment of rules for each member of the Sobat Icad community to always upload content based on facts without exaggeration. In future research, the researchers hope to explore the perspectives of both supportive and opposing communities to examine the social dynamics through the public's response regarding the organization of campaign support for Richard Eliezer as a justice collaborator.